An Analysis of Azyumardi Azra’s Thought on Islamic Identity in the Era of Globalization - Abdul Fadhil; Rio Permata; Ma’wah Salsabila; Taftazani Ulya Fauzan; Marseli Nurul Alifya (Universitas Negeri Jakarta, 2025)
This study aims to analyze Azyumardi Azra’s thoughts on Islamic identity in the context of globalization. It employs a qualitative method using the Islamic thought approach through literature review and thematic analysis. Azra views globalization as both a challenge and an opportunity for Muslims, especially in Indonesia, to develop a religious identity that is adaptive to contemporary changes. Through the concept of Islam Nusantara, Azra emphasizes the indigenization of Islam by integrating religious values with local cultural traditions, resulting in a moderate, inclusive, and tolerant form of Islam. Muslim identity in Indonesia is shaped by the dynamic interaction between Islamic teachings and the country’s socio-cultural realities. This study also connects Azra’s ideas with the perspectives of other thinkers such as Clifford Geertz, Robert W. Hefner, and Nurcholis Madjid to enrich the understanding of contextual Muslim identity. The findings affirm that Islamic identity is dynamic and continues to evolve through dialogue between religious tradition and the demands of a globalized world.